Design, synthesis and evaluation of indazoles as antiproliferative agents - Cotter, Tadhg S. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2015)
Cancer is a leading cause of death in most countries, second only to the diseases of the circulatory system. In relation to Ireland, cancer accounted for 29.6 % of all the deaths reported in 2012. After non-melanoma skin cancer, breast cancer is the most common cancer suffered by women in Ireland. In 2012, there were 2,899 reported new cases of breast cancer while 704 female deaths were associated with this disease. Ireland has one of the highest rates of incidence of breast cancer in Europe.
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin